On evidence and rational beliefs : a thesis in defence of intrapersonal uniqueness - Ng, Sarah Sin Ci (Nanyang Technological University, 2021)
There are three doxastic attitudes an agent can adopt in response to a given proposition: to believe, to not believe or to withhold judgement. What can we conclude about the individual rationality of the agents who, in response to the same set of evidence, come to adopt incompatible doxastic attitudes towards a target proposition? If there exists a uniquely rational doxastic attitude that should be adopted in response to a set of evidence, then we can grant that at most one agent is being rational in any belief-disagreement cases (viz., Uniqueness). Otherwise, we can grant that more than one agent is being rational in belief-disagreement cases (viz., Permissivism). This paper defends two claims: §1 defends a specific variation of Uniqueness that has no interpersonal import (viz., Intrapersonal Uniqueness). For a particular person, there is only one doxastic attitude she can rationally hold towards a proposition based on the evidence. §2 argues that Intrapersonal Uniqueness is reconcilable with the idea of intersubjective reasonable disagreements, a phenomenon that has interpersonal import. On this view, reasonable disagreements persist, not because the evidence is permissive in what it supports, but because total evidential sharing among agents is an impossibility.